Efektivitas pemberian hormon pertumbuhan rekombinan ikan kerapu kertang (Epinephelus lanceolatus, Bloch 1790) melalui perendaman dan oral terhadap pertumbuhan elver ikan sidat (Anguilla bicolor bicolor) - Alimuddin Alimuddin; Boyun Handoyo; Nur Bambang Priyo Utomo (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2014)
Indonesian eel (Anguilla bicolor bicolor) has recently been cultivated intensively in Indonesia. The growth of Indonesian eel is slow. This study was performed to determine a proper delivery method of recombinant giant grouper (Epi-nephelus lanceolatus) growth hormone (rElGH) and observe aquaculture and nutrient related performances of Indonesian eel elver after rElGH treatment. Three delivery methods of rElGH, namely immersion, orally, and combination of immersion and orally were tested. The dosage of rElGH by immersion (12 mg L